Assessments of Nitrate Budgets in the Yellow Sea Based on a 3D Physical-Biogeochemical Coupled Model - Tak, Yong-Jin; Cho, Yang-Ki; Hwang, Jeomshik; Kim, Yong-Yub (Frontiers in Marine Science, 2022)
Nitrate (NO3–) plays an important role in ecosystems and aquaculture in the Yellow Sea (YS). Sparse observational data suggest that ocean currents and nitrification are crucial to NO3– flux in the YS; however, a quantitative assessment of these fluxes has not yet been performed. This study investigates seasonal and spatial variations in NO3– flux via currents and biological processes in the YS from 2006 to 2019 using a physical-biogeochemical coupled model. The model results show that the current-driven fluxes exceeded biological processes in the eastern and central regions of the YS, unlike in the western and northern regions. Advection of NO3– in the YS is mainly driven by cyclonic circulation in summer and fall, and anticyclonic circulation in spring and winter. The Subei Coastal Current along the coast of China plays a primary role in net advective influx of NO3– to the YS year round. The NO3– influx by the Yellow Sea Warm Current along the lower layer of the southcentral YS is offset by outflux through wind-driven surface currents in winter. The southward movements of the Yellow Sea Bottom Cold Water in summer and the Korean Coastal Current in winter are major NO3– outfluxes to the East China Sea. In terms of biological processes, NO3– is mainly consumed by phytoplankton during the spring bloom and supplied through organic matter decomposition and nitrification. Net supply of NO3– by biological processes was the greatest in the southcentral YS where the Yellow Sea Bottom Cold Water is present.